Evaluation of Antimicrobial Susceptibility Pattern of Pseudomonas Aeruginosa with Special Reference to MBL Production in Tertiary Care Hospital (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: bacterial infection; carbapenem resistance; carbapenemase; mbl producers; multi drug resistance; pseudomonas aeruginosa; routinely used antibiotics; n